2018
DOI: 10.1242/jeb.170670
|View full text |Cite
|
Sign up to set email alerts
|

Cold temperature represses daily rhythms in the liver transcriptome of a stenothermal teleost under decreasing day length

Abstract: The climate-change-driven increase in temperature is occurring rapidly and decreasing the predictability of seasonal rhythms at high latitudes. It is therefore urgent to understand how a change in the relationship between photoperiod and temperature can affect ectotherms in these environments. We tested whether temperature affects daily rhythms of transcription in a cold-adapted salmonid using high-throughput RNA sequencing. Arctic char () from a subarctic population were reared at a high and a low temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 64 publications
0
16
0
Order By: Relevance
“…Published male Arctic Charr liver transcriptome data was then compared to the network to evaluate cross-species module preservation (Prokkola et al 2018). Even with caveats regarding sample size (see Methods), several female Brook Charr modules were highly preserved in Arctic Charr males, including blue2 (Zsummary = 34), green (Zsummary = 24), and salmon (Zsummary = 17), also the most conserved in male Brook Charr (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Published male Arctic Charr liver transcriptome data was then compared to the network to evaluate cross-species module preservation (Prokkola et al 2018). Even with caveats regarding sample size (see Methods), several female Brook Charr modules were highly preserved in Arctic Charr males, including blue2 (Zsummary = 34), green (Zsummary = 24), and salmon (Zsummary = 17), also the most conserved in male Brook Charr (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The broodstock of this population was reared in hatchery conditions for three generations after being collected from a subarctic, land-locked population in Finland (Lake Kuolimo, 61°16′ N; 27°32′ E). The data were collected from nine male liver samples (fish relatedness not known) from each of 8 o C and 15 o C (total = 18 samples), but due to a large effect of temperature on the transcriptome, and differences between sampling times in the 15 o C group, only the nine samples from the 8 o C, group were used here (normal rearing temperature during summer at the fish hatchery; Figure S2) (Prokkola et al 2018). Fish body mass at 8°C was on average 24.2 g ± standard deviation (S.D.)…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, it has recently been shown that the daily variation of transcription in a polar salmonid, the Arctic char (Salvelinus alpinus), is much reduced after a 1 month acclimation to 8°C in comparison with acclimation to 15°C (Fig. 2) (Prokkola et al, 2018).…”
Section: Climate Change and Biological Rhythms Circadian Rhythmsmentioning
confidence: 98%